Goldenhar syndrome with right circumflex aortic arch, severe coarctation and vascular ring in a twin pregnancy - Elaheh Malakan Rad (Wolters Kluwer Medknow Publications, 2014)
Goldenhar syndrome (GS) or oculo-auriculo-vertebral dysplasia (OAVD), involves a wide variety of organ systems. Cardiovascular anomalies are among the frequent malformations. The purpose of this report is to introduce a male case of a dizygotic twin pregnancy with GS and right circumflex aortic arch (RCAA), severe coarctation, hypoplastic aortic arch, aberrant right subclavian artery, vascular ring, bilateral renal artery stenosis, and mild Dandy-Walker syndrome. The embryology of RCAA and coarctation is revisited.